Uma abordagem metodológica para ensino de banco de dados conceitual com uso de bases da língua portuguesa em cursos técnicos de informática na educação profissional tecnológica - Montenegro, Toni Ferreira (2022)
The use of communication technologies - ICTs in the daily life of society has been a reality for some time with extreme efforts in the process of adaptation of human beings and the constant transformations in their social changes. The computer and the internet, for example, have a great impact on the means of production, on the processes of impact on the means of work, on education, on the media and on many other economic, social and cultural sectors. Through this, the objective of the study was to investigate, understand and apply the conceptual modeling project of the Database as a tool to improve textual interpretation in technical high school in the area of computing. The development of classroom intervention research and the entire methodological process of this work are guided and grounded in design principles that follow the characteristics of activities planned in EDR. Both the definition of the problem and the analysis of the results, the research takes into account the elements for academic production, regarding the creation of learning based on theoretical bases applied and validated in practice. A set of three Didactic Activities for the interpretation of Database problems were developed and executed in a virtual classroom for students in the second and third year of the technical course in informatics integrated into High School. Such activities obtained significant results with regard to the context of applicability, design and development of practices in the areas addressed in the study, however, there are still many gaps to be filled through multidisciplinary studies that promote the development of teaching in the school niche presented .